Women in Barangay governance experiences from selected women Punong Barangays in Miagao, Iloilo. - Tambasen, Renzie Mae
This study delves into the life stories and experiences of selected women Punong Barangay in Miagao, Iloilo. It identifies and analyzes the structural, institutional and cultural factors that facilitated and hinderedwomen's entry into local governance. It also identifies the challenges that women leaders have encountered upon assumption into office and during their incumbency. This study also examines the measures and strategies they initiated that promoted gender mainstreaming and enhanced women's partiicpation in local development. The study featured experiences of four selected women Punong Barangays from Malagyan, San Jose, Tigmalapad, and Oyungan. This study used life story as a methology in exploring their individual experiences as women leaders. Key informant interview, field observation and secondary data were used as information gathering tools. A number of cultural, structural, and institutional factors have been identified to have indered or facilitated their entry into the political sphere. They also faced the challenge of multiple burden and discrimination from the barangay council. Irabilities to mainstream gender concerns were also affected by the lack of guidance from the Municipal government. These challenges are deeply rooted to the lack of assistance from the Municipal government.